The utilization of educated manpower in industry: a preliminary report - Blaug, Mark.; Peston, Maurice; Ziderman, Adrian (London: Oliver & Boyd, 1967)
In 1964-65, the industrial manpower project made a pilot study of the relationship between the economic performance of British industrial firms and the education of their workers. Through intensive study of five firms, age-earnings profiles for various educational levels were drawn up, with sufficient information to draw up tentative profiles for the United Kingdom. The pilot project was considered to be of value since it showed up limited economic theory, scarce and incomplete data, and the need for direct contact with firms. It was concluded that education in Britain has a positive rate of return, especially at the middle pre-degree level, firms should stress career planning for their employees, labor costs should increasingly be converted to fixed costs, and flexibility of educational requirements for each occupation should be studied. The government could remedy the lack of personnel data by furnishing firms with standardized record-keeping procedures and occupational and educational classifications.
Bibliographical footnotes.
rpm 21/02/2018
Loans
Keywords: Professions; Electrical engineers